2021
DOI: 10.2196/24457
|View full text |Cite
|
Sign up to set email alerts
|

Malay Version of the mHealth App Usability Questionnaire (M-MAUQ): Translation, Adaptation, and Validation Study

Abstract: Background Mobile health (mHealth) apps play an important role in delivering education, providing advice on treatment, and monitoring patients’ health. Good usability of mHealth apps is essential to achieve the objectives of mHealth apps efficiently. To date, there are questionnaires available to assess the general system usability but not explicitly tailored to precisely assess the usability of mHealth apps. Hence, the mHealth App Usability Questionnaire (MAUQ) was developed with 4 versions accord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 31 publications
4
46
0
Order By: Relevance
“…(3) different functions of the tested interactive mHealth apps used by patients (with vs without the chatbot function); and (4) respondents' experience with mHealth apps. Similarly, we found that the reliability of the I-C-MAUQ was relatively higher than those reported in Mustafa et al [13] (Cronbach α=.946; corrected item-total correlation values between -0.057 and 0.868) and Zhou et al [9] (Cronbach α=.914). We once again attributed the reliability difference to the aforesaid 4 factors, which will be discussed in the following sections.…”
Section: Principal Findingssupporting
confidence: 62%
“…(3) different functions of the tested interactive mHealth apps used by patients (with vs without the chatbot function); and (4) respondents' experience with mHealth apps. Similarly, we found that the reliability of the I-C-MAUQ was relatively higher than those reported in Mustafa et al [13] (Cronbach α=.946; corrected item-total correlation values between -0.057 and 0.868) and Zhou et al [9] (Cronbach α=.914). We once again attributed the reliability difference to the aforesaid 4 factors, which will be discussed in the following sections.…”
Section: Principal Findingssupporting
confidence: 62%
“…It is mainly used to study the usability of digital healthcare systems. Its standalone patient version has been translated into the Malaysian version, and it has shown an acceptable practicability (Mustafa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly used to study the usability of digital healthcare systems. Its standalone patient version has been translated into the Malaysian version, and it has shown an acceptable practicability ( Mustafa et al, 2021 ). However, China has not yet introduced a Chinese version of the MAUQ, the present study aimed to translate and verify the patient version of the interactive mHealth app usability questionnaire (MAUQ) into Chinese, and to provide a usability testing tool for developers of mHealth apps in China.…”
Section: Introductionmentioning
confidence: 99%
“…The Malay-mHealth App Usability Questionnaire (M-MAUQ) will be used [ 46 , 50 ] to evaluate the feasibility and usability of the app. This questionnaire will assess the ease of use, interface, satisfaction, and mHealth app usefulness to the study participants.…”
Section: Methodsmentioning
confidence: 99%
“…(8) What motivates you to continue the PFMT? (Further information will be collected via qualitative data feedback) Malay-mHealth App Usability Questionnaire (M-MAUQ) will be used [46,50] to assess the ease of use, interface, satisfaction, and the usefulness of mHealth apps to the end user. Secondary Outcomes Information The log system records.…”
Section: Primary Outcome Informationmentioning
confidence: 99%